THE REPRESENTATION OF WOMAN IN SUPERHERO MOVIE ENTITLED “BIRDS OF PREY” BY CATHY YAN - Azi, Rahmawati; Nurmalasari, Fitriananingsih; Aso, La (Seshiski: Southeast Journal of Language and Literary Studies, 2021)
This study aims to analyze the representation of woman in "Birds of Prey" movie. The problem in this study is how is woman represented in the superhero movie entitled “Birds of Prey”. The research method is the qualitative method. Power Feminism Theory from Naomi Wolf’s is used to analyze the data. This research analized therepresentation of woman in Birds of Prey movie by Cathy Yan. The data was collected through watching the movie, screenshotting, classifying, and previewing. This study found that women named Harley Quinn as the main character in the Birds of Prey movie is represented as a superpower Women. The characterization of a superpower can be denoted through; (1) emancipating herself from the domination of man, (2) enhancing her femininity as outstanding, (3) women as super heroin, (4) being free from Joker’s shadow. It is suggested that Birds of Prey tried to replace the man role as the dominant figure in the superhero genre films.